Los pensamientos son libres: Susan Hiller y las letras par a una comunidad posible - Soto Rivera, Paulina (Revista de Teoría del Arte, 2017)
In the current cultural context, Susan Hiller’s die Gedanke Sind Frei (Los pensamientos son libres, 2012), an installation based on transnational folklore marks a breaking point regarding debates of arts across academic debates. The works as well as its social responses address the Arts Academy ideologies, and discourses on art readings. Set on documenta 2012, the works still establish a paradigm thachallenges settled ideas regarding the crisis of contemporary social life. It points out to utopian social ideas, music, and ideals that persist over time.